(untitled) (Journal of Mathematical Study, 2021)
In this paper, we are concerned with a show the existence of a entropy solution to the obstacle problem associated with the equation of the type : cases Au+g(x,u,∇u) = f & in & Ω u=0 & on & ∂Ω cases where Ω is a bounded open subset of R^N, N≥ 2, A is an operator of Leray-Lions type acting from W_0^1,p(.) (Ω, w(.)) into its dual W_0^-1,p'(.) (Ω, w^*(.)) and L^1 - deta. The nonlinear term g : Ω× R× R^NR satisfying only some growth condition.